Sistem Pendukung Keputusan Dalam Penentuan Jabatan Kapolres Di Jajaran Kepolisian Daerah Sumatera Utara (Polda Sumut)Dengan Metode Simple Additive Weight (SAW) - Jijon Raphita Sagala; Guntur Syahputra (Jurnal Mantik Penusa, 2018)
Office in policing in the functions of Office, started after the Organization carry out the withdrawal and selection, that is, at the moment a prospective member of the police force was declared acceptable and ready to be placed on the Office or work unit in accordance with the educational unit.But it turns out that the problem is not that simple, because it is precisely the success of the overall program of the election office is located on the accuracy in placing personnel concerned.The placement process is a process that is crucial in getting the competent Office is required, because the proper placement will be able to help companies or agencies in achieving the expected objectives. With the method of Simple Additive Weighting (SAW) can assist decision makers in selecting prospective Kapolres who really fit the criteria required by police agencies.So with this system of North Sumatra Police can minimize errors caused by the performance of the Police Personnel, that is, by the way puts personnel at the position or field in accordance with its ability. Keywords: Simple Additive Weighting (SAW), Kapolres, Decision Support System